The effectiveness of the use of Tantum Verde® in the stages of occupational hygiene oral cavity - Petrushanko, T.; Popovich, I. (Actual Dentistry, 2018)
Relevance. The main component of prevention and treatment of dental diseases is professional oral hygiene, which requires the use of local medication support in the form of an anti-inflammatory drug. Purpose: to study the effectiveness of topical application of the drug Tantum Verde® in patients with professional oral hygiene. Materials and methods. Clinical, X-ray studies of the use of the drug Tantum Verde® and alcohol solution of marigold tincture were performed in 64 patients aged 18–40 years who underwent professional oral hygiene using ultrasound technology in the dynamics of seven days of treatment for indicators of the clinical condition of periodontal, hygienic, periodontal indices. Results. The conducted studies showed a positive dynamics of disappearance of inflammatory gum reactions in both groups, but in terms of they were twice as fast in patients receiving Tantum Verde®, which was confirmed by the results of a subjective and objective examination and indices of periodontal indices. Conclusions. It is established that the use of Tantum Verde® with professional oral hygiene and further local medical treatment inflammatory reactions of gums not only contributes to the analgesic effect, but also accelerates the disappearance of exudative changes in the gums and is evidence of a qualitative anti-inflammatory effect of the drug with no adverse reactions. Complex positive impact Tantum Verde® on the condition of the gums, especially at the stages of professional hygiene of the oral cavity, necessitates its wide introduction into practice of dentists. Key words: Tantum Verde®, professional oral hygiene, anti-inflammatory therapy